Evaluation of community level interventions to address social and structural determinants of health: a cluster randomised controlled trial - Wall, Martin; Hayes, Richard; Moore, Derek; Petticrew, Mark; Clow, Angela; Schmidt, Elena; Draper, Alizon; Lock, Karen; Lynch, Rebecca; Renton, Adrian (BioMed Central, 2009)
Background: In London and the rest of the UK, diseases associated with poor diet, inadequate physical activity and mental illness account for a large proportion of area based health inequality. There is a lack of evidence on interventions promoting healthier behaviours especially in marginalised populations, at a structural or ecological level and utilising a community development approach. The Well London project financed by the Big Lottery 'Wellbeing' Fund and implemented by a consortium of London based agencies led by the Greater London Authority and the London Health Commission is implementing a set of complex interventions across 20 deprived areas of London. The interventions focus on healthy eating, healthy physical activity and mental health and wellbeing and are designed and executed with community participation complementing existing facilities and services. Methods/Design: The programme will be evaluated through a cluster randomised controlled trial. Forty areas across London were chosen based on deprivation scores. Areas were characterised by high proportion of Black and Minority Ethnic residents, worklessness, ill-health and poor physical environments. Twenty areas were randomly assigned to the intervention arm of Well London project and twenty 'matched' areas assigned as controls. Measures of physical activity, diet and mental health are collected at start and end of the project and compared to assess impact. The quantitative element will be complemented by a longitudinal qualitative study elucidating pathways of influence between intervention activities and health outcomes. A related element of the study investigates the health-related aspects of the structural and ecological characteristics of the project areas. The project 'process' will also be evaluated. Discussion: The size of the project and the fact that the interventions are 'complex' in the sense that firstly, there are a number of interacting components with a wide range of groups and organisational levels targeted by the intervention, and secondly, a degree of flexibility or tailoring of the intervention, makes this trial potentially very useful in providing evidence of the types of activities that can be used to address chronic health problems in communities suffering from multiple deprivation. Trial Registration: Current Controlled Trials ISRCTN68175121
Keywords: Public health; Intervention; Deprivation; Health inequality; Community; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321299 Public health and health services not elsewhere classified